A rare case of foreign body in coronary sinus. A novel endovascular method for retrieval - Maturi, Bhanu; Sharma, Ashwini; Runkana, Ashok; Rajasekaran, Rhoshini; Kondapaneni, Varshitha; Parajuli, Tilachan (Journal of Cardiology and Cardiovascular Medicine, 2023)
Central venous catheter fracture and migration are rare complications in patients receiving long-term infusions or chemotherapy. We present a rare case of a chest port catheter fracture that migrated into the coronary sinus. This case is likely the fourth report of a port catheter fracture with migration to the coronary sinus. Because of the difficult-to-retrieve location, multiple attempts were unsuccessful with traditional techniques using a loop snare. Finally, the fractured portion was disengaged from the coronary sinus using a navigational electrophysiology catheter guided by intracardiac echocardiography; the dislodged end was snared and eventually removed by the femoral route. This case of a chest port catheter fracture is unique because of the unusual migration to the coronary sinus and the use of a navigational electrophysiology catheter as a novel retrieval technique.